Pemanfaatan Teknologi Informasi dalam Peningkatan Layanan Administrasi di Kantor Kecamatan Ilir Barat Dua Kota Palembang - Putra Perdana; Rozali Ilham (Politeknik Kampar, 2025)
This study aims to analyze the utilization of information technology in improving administrative services at the Ilir Barat Dua Sub-district Office in Palembang City. The implementation of information technology in government administration has become an essential requirement in the digitalization era in accordance with Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems. The research method uses a descriptive qualitative approach with data collection techniques in the form of literature studies, observations, and interviews. The results show that the utilization of information technology at the Ilir Barat Dua Sub-district Office has shown significant progress in administrative service aspects, although challenges still exist in terms of human resource competencies and supporting infrastructure. Based on these findings, this study recommends intensification of office application training programs and administrative information systems for village apparatus as well as improving the quality of information technology infrastructure to ensure effective services to the community.